Digital image processing: concepts, algorithms, and scientific applications - Jähne, Bernd (Springer Berlin Heidelberg Imprint: Springer, 1997)
Since the first edition of this book was published in 1986 computers have become more powerful and at the same time less expensive, so that widespread applications for digital image processing emerge. The presentation and the selection of materials is guided by the needs of a researcher who wants to apply image processing techniques in his or her field. In this sense the book offers an integral view of image processing from image acquisition to the extraction of of the data of interest. The discussion of the general concepts is supplemented with examples from applications on PC-based image processing systems and ready-to-use implementations of important algorithms. These examples, images as well as exercises for selfstudy along with a hands-on version of the image processing software "heurisko" can be found on the enclosed CD-ROM